BUMPY STEM Is an Arabidopsis Choline/Ethanolamine Kinase Required for Normal Development and Chilling Responses - Rabeler, Christina; Chen, Mingjie; Kaplinsky, Nick (Frontiers in Plant Science, 2022)
Phospholipid biosynthesis is a core metabolic pathway that affects all aspects of plant growth and development. One of the earliest step in this pathway is mediated by Choline/Ethanolamine Kinases (CEKs), enzymes in the Kennedy pathway that catalyze the synthesis of the polar head groups found on the most abundant plant phospholipids. The Arabidopsis genome encodes four CEKs. CEK1-3 have been well characterized using viable mutants while CEK4 encodes an essential gene, making it difficult to characterize its effects on plant development and responses to the environment. We have isolated an EMS-induced allele of CEK4 called bumpy stem (bst). bst plants are viable allowing the effects of decreased CEK4 function to be characterized throughout the Arabidopsis life cycle. bst mutants have a range of developmental defects including ectopic stem growths at the base of their flowers, reduced fertility, and short roots and stems. They are also sensitive to cold temperatures. Supplementation with choline, phosphocholine, ethanolamine, and phosphoethanolamine rescues bst root phenotypes, highlighting the flow of metabolites between the ethanolamine and choline branches of the Kennedy pathway. The identification of bst and characterization of its phenotypes defines new roles for CEK4 that go beyond its established biochemical function as an ethanolamine kinase.